1996
DOI: 10.1097/00000542-199605000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Glutamate Receptors in Strychnine- and Bicuculline-induced Allodynia in Conscious Mice

Abstract: These results demonstrate that both strychnine- and bicuculline-evoked allodynia were mediated through pathways that include the glutamate receptor and nitric oxide systems but in a different manner. the current study suggests that GABA and glycine may modulate responses to an innocuous tactile stimulus as inhibitory neurotransmitters at presynaptic and postsynaptic sites in the spinal cord, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 30 publications
3
22
0
Order By: Relevance
“…Higher doses of strychnine (>10.0 μg) may cause seizure. Consistent with previous studies (13,17,41,42), intrathecal strychnine induced marked mechanical allodynia in a dose-dependent manner ( Figure 7E). However, only the highest subconvulsive dose of strychnine (10 μg) induced thermal hyperalgesia ( Figure 7F).…”
Section: Activation Of Low-threshold Aβ Fibers Evokes Ap Output Of Nosupporting
confidence: 92%
“…Higher doses of strychnine (>10.0 μg) may cause seizure. Consistent with previous studies (13,17,41,42), intrathecal strychnine induced marked mechanical allodynia in a dose-dependent manner ( Figure 7E). However, only the highest subconvulsive dose of strychnine (10 μg) induced thermal hyperalgesia ( Figure 7F).…”
Section: Activation Of Low-threshold Aβ Fibers Evokes Ap Output Of Nosupporting
confidence: 92%
“…Either the blockade of inhibitory neurotransmission by GABA and glycine (34,35) or augmentation of pain transmission by the excitatory transmission by the glutamate-NO system (36, 37) is known to induce allodynia. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GABAergic neurons are present in laminae I-III of the spinal cord, and many of the neurons with somata in laminae I-III are inhibitory interneurons containing GABA (43). We previously suggested that both PGE 2 -and bicuculline-induced allodynia were mediated through pathways that include the glutamate receptor-NO system (35)(36)(37). The induction of allodynia was considered to result from removal of tonic or evoked inhibition from pathways relaying information about innocuous stimuli and augmentation of pain transmission by the excitatory transmission by the glutamate-NO system.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the difference in kinetics of the GABAergic versus glycinergic IPSCs and the type of activity that recruit them may match the nature of excitatory input they control. Interestingly, metabotropic receptor antagonists attenuate bicuculline-induced allodynia but are not effective against strychnine-induced allodynia (Onaka et al, 1996). Metabotropic glutamate receptors appear to be mainly located at extrasynaptic sites (Baude et al, 1993) and may therefore be activated selectively after release of a sufficient concentration of glutamate that can spill over the synapses (Rusakov and Kullmann, 1998).…”
Section: Functional Significance Of the Difference In Gaba A Rand Glymentioning
confidence: 99%